Parasitism by Cryptosporidium spp. in domestic canine in the city of Pelotas, Rio Grande do Sul, Brazil (Research, Society and Development, 2021)
Cryptosporidium spp. are protozoa, of the Apicomplexa phylum, capable of infecting different species of vertebrates, such as mammals, birds, reptiles, fish, amphibians and also man, as it has zoonotic potential, being the causative agent of Cryptosporidiosis. Infection occurs through ingestion of sporulated oocysts present in contaminated water or food, or through contact with feces of infected animals. Clinical signs, when present, are gastroenteritis, such as diarrhea, vomiting, fever, abdominal cramps and loss of appetite, both in animals and in humans. Therefore, the aim of this work was to report the case of a dog infected with Cryptosporidium spp., diagnosed through coproparasitological examination. The material analyzed came from a dog, adult, male, SRD, with a history of diarrhea, with blood and mucus, sporadic episodes of vomiting were also reported. It was also informed that the animal had its deworming and vaccination schedule updated. In the coproparasitological techniques of Willis Mollay, Faust and HPJ, no evolutionary forms of any genus of enteroparasites were observed. To investigate Cryptosporidium spp., the centrifuge sedimentation technique in formalin-ether was performed first to concentrate the oocysts and later, for identification, the modified Ziehl-Neelsen staining, where it was possible to visualize the protozoan oocysts. As a treatment, off label use of Azithromycin (10 mg/kg), VO, 24x24 hours, for 7 days, and probiotic, (5 gr.), 24x24 hours, for 5 days, was recommended. After the end of therapy, there was clinical improvement in the patient and after a new coproparasitological analysis, no oocysts of Cryptosporidium spp.